The Determination of Socioeconomic Situations that Affect the Life Conditions of Poor Households: The Case of Elazığ - Kılınç, Pelın; Demir, Merve Sefa (My University, 2023)
In this study, a descriptive analysis of the socio-economic status of poor households was made in order to reach human-level needs. Thus, it has been tried to determine how poverty affects the living conditions of individuals. The study is important in terms of revealing how poverty deepens the living conditions of the households living in poverty and revealing this with the expressions and experiences of the poor individuals. The sample of the research consists of forty-five households determined by the snowball technique, one of the purposeful sampling methods. Only one of the parents in each household was interviewed. The data of the research is based on the results of the data obtained from the semi- structured interview form. The study is qualitative research and also a case study based on the descriptions. As a result of this study that was conducted to understand how the life profiles and conditions of the poor individuals more accurately, it is determined that individuals experience poverty quite deeply. In this study, in which it is tried to consider the indicators of poverty from a household- based and individual perspective, it has been tried to determine the socio-economic status of the households, their deficiencies in basic needs such as shelter, nutrition, clothing, and their neediness. Keywords: Poverty, indicator of poverty, living conditions of the poor, socio economic profile, poverty in Elazığ
Keywords: Sosyal Çalışma; İktisat